FC 115: Long-Term Outcomes in Eculizumab-Treated Kidney Transplant Patients Enrolled in the Global Atypical Haemolytic Uraemic Syndrome Registry. (3rd May 2022) - Gema Ariceta Iraola, Maria; Al-Dakkak, Imad; Anokhina, Katerina; Ardissino, Gianluigi; Greenbaum, Laurence A; Kumar, Gurinder; Licht, Christoph; Siedlecki, Andrew; Van de Walle, Johan
Abstract: BACKGROUND AND AIMS: The global atypical haemolytic uraemic syndrome (aHUS) registry (NCT01522183), the largest repository of real-world data on patients with aHUS, provides key insights into disease course, natural history, and patient (pt) outcomes with and without complement inhibitor therapy. Prior to eculizumab availability, pts with aHUS had a reportedly high risk of disease recurrence and graft loss following a kidney transplant (KTx). We report the long-term clinical outcomes of eculizumab-treated pts who received a KTx. METHOD: This analysis included pts enrolled from April 2012–November 2021. Pts were included in a long-term treatment outcomes study if they had ever been treated with eculizumab and were excluded if they had DGKE mutations or their diagnosis was later revised to any condition other than aHUS. The current analysis set included pts who had received a KTx no more than 30 days prior to eculizumab start or up to 60 days post eculizumab start date, had ≥3 years of follow-up (FU) post-transplant and had serum creatinine (SCr) measurements at baseline (BL) and post 3 years FU. Changes in kidney function, haematological parameters and clinical characteristics at last follow-up (LFU) were assessed. RESULTS: A total of 329/1970 adult and paediatric registry pts met the inclusion criteria and received a KTx; 78 pts from 12 countries met sub-group inclusion criteria. BL demographics are shown in Table 1 . Mean (SD) treatment duration was 5.7 (2.4) years and 47 (60%) pts had pathogenic genetic variants. Lab parameters at BL (closest measurement at or following KTx) and LFU are reported in Table 2 . Despite large ranges, median SCr levels remained stable at LFU. Median eGFR and platelet levels were similar at BL and LFU, while lower median lactose dehydrogenase levels were seen at LFU. At LFU: four pts (5%)—three adult—had subsequent KTx(s); eight (10%)—seven adults—had received dialysis by last observation; and two (3%) had received plasma exchange/infusion. Two pts (3%) died during the observation period. CONCLUSION: This study assessed a large, real-world population of pts at high risk of KTx failure. Lab parameters suggest most pts benefitted from eculizumab treatment, with few TMA-related complications and stable kidney function and haematological parameters for ≥3 years. Overall, the proportions of female pts and of pts with pathogenic genetic variants were consistent with previous studies. A potential study limitation was the relatively stringent sub-population-specific inclusion criteria. However, these data further demonstrate the beneficial impact of eculizumab treatment in the long-term management of aHUS in pts requiring KTx.